Limites objetivos e eficácia preclusiva da coisa julgada - Santos, Bruno Ricardo Guite de Melo e (2015)
It approaches the concept, scope, rationale and evolution history of the processual Institute of res judicata, addressing its various classifications and the treatment given to the matter by the national legislation (Law No. 5,869, of January 11, 1973) and the New Code of Civil Procedure (Law No. 13,105 / 15), in addition to major doctrinal positions and jurisprudence on the subject,focusing on so-called objective limits and preclusive effect of res judicata and directed application to the study of individual actions. Differentiation between res judicata and terms or similar figures, definition of its objective limits and determination of the legal requirements and time of formation of the two especies of res judicata. Study of res judicata in light of thepreclusive effect and concepts of merit, dispute, sentence device and other related issues raised by contemporary national doctrine. Analysis of current issues involved with the theme, such as the formation of res judicata in successive tract actions, the existence of partial judged things, the positive and negative effects of res judicata and the questions and issues implicitly resolved in demands and their relationship with the formation of res judicata, among other controversial points made doctrine and jurisprudence and suggestions of national doctrine for its solution. Study of the innovations brought to the matter by the New Civil Procedure Code (Law No. 13,105 / 15), with the realization of which solutions were actually accepted and introduced in the legislative text of the new law